PENGARUH ECONOMIC VALUE ADDED, MARKET VALUE ADDED, RESIDUAL INCOME, EARNINGS DAN ARUS KAS OPERASI TERHADAP RETURN SAHAM (Studi Empiris pada perusahaan LQ-45) - Hari Cahyadi; Akhmad Darmawan (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2016)
This study to get empirical evidence that the EVA, MVA, Residual income, Earnings and operating cash flow affect the return earned by shareholders, either partially or simultaneously. The sampling method used was purposive sampling, with the criteria of the company that is always inclouded in the LQ-45 index listed in the Indonesia Stock Exchange (BEI) during the observation period of 2011-2014. Companies used in the sample have a positifve data. The analytical method used was multiple linear regression test. The result of this study concluded that the MVA, residual income and operating cash flows simultaneously affected the return earned by shareholders. MVA partially had no effect on returns received by shareholders. Residual income partially had an effect on returns received by shareholders. Operating cash flow partially had an influence on return received by shareholders. The second and the fifth hypothesis in this study could not be tested because EVA variables and earnings experienced multi co linearity, thus it was excluded from the study. Keywords : EVA, MVA, Residual income, Earnings, operating cash flows and stock returns